(untitled) (Fiep Bulletin - online, 2013)
The National Consensus of Ergometry recommends the use of the front handrail in order to minimize any possibility of imbalance and falls during the assessment of cardio respiratory fitness, however, holding on this rail can reduce the energy expenditure during the activity allowing the person to remain longer on the treadmill, reflecting the possibility of achieving higher VO2max values ??when compared to the test without using the rail, allowing different final values ??of VO2max. Therefore this study aimed to compare the cardio respiratory fitness of persons on the treadmill with and without the assistance of the handrails. The sample consisted of 9 male volunteers with the average age of 33 years, practicing regular physical activity, residents of the metropolitan area of ??Vale do Aço. All volunteers were submitted to both ergoespirometric tests on a Inbramed Millennium Super ATL (Inbrasport) treadmill following a ramp protocol, one using the front handrail (TWS) and the other without the use of the front handrail (TWOS). For the present study it was used descriptive statistics and to check the difference among the average results the "t" Student test was applied on paired samples with significance level of p <0.05. There was not a significant statistical difference in any of cardio respiratory varies collected in both tests, but there was a significant difference on the duration of the test. It is concluded that the use of the rail during the test did not affect the cardio respiratory variables, despite of the time TWS was more extensive than in the TWOS.